Vulvar Lobular Capillary Hemangioma: A Rare Location for a Frequent Entity - Case Report - Abreu-dos-Santos, F (2016)
Lobular capillary hemangioma, or pyogenic granuloma, is an acquired hemorrhagic benign vascular lesion of the skin and mucous membranes. The pyogenic granuloma of the vulva is a rare finding and a limited number of case reports are available in the literature. To the best of our knowledge this is the first case described as a single pyogenic granuloma on the vulva.